2020
DOI: 10.4103/jispcd.jispcd_293_19
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Lifestyles on Dental Caries of Adult Patients in Udupi District: A Cross-Sectional Study

Abstract: A BSTRACT Background: Dental caries is preventable if favorable health behavior is successfully established. Exploring the broader concept of lifestyle will be useful to determine that how lifestyle of people can affect dental caries. Aim: The aim of this study was to determine the impact of overall lifestyle of an individual (analyzed using health practice index) on dental caries of adult population. Material and Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…Likewise, not visiting a dentist to address oral health issues has been associated with a higher propensity for oral diseases, such as dental caries [32]. In addition, it has also been demonstrated that there is association between tooth loss and OHRQoL, which is lower in individuals who have experienced more tooth loss over time [25].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, not visiting a dentist to address oral health issues has been associated with a higher propensity for oral diseases, such as dental caries [32]. In addition, it has also been demonstrated that there is association between tooth loss and OHRQoL, which is lower in individuals who have experienced more tooth loss over time [25].…”
Section: Discussionmentioning
confidence: 99%
“…Singla N et al (23) halló en un estudio realizado en 800 sujetos con edades entre 20 y 50 años, que los participantes con nivel económico más bajo, de mayor edad, desempleados, de sexo femenino, con menor educación, menor frecuencia de cepillado dental, estilo de vida pobre o moderado, tienen mayor riesgo de tener caries dental. En este estudio se encontró que la mayoría de los participantes tenían un estilo de vida poco saludable y un CPOD muy alto, sin embargo no se halló asociación estadística entre el estilo de vida y la presencia de caries dental.…”
Section: Discussionunclassified
“…Another factor related with dental caries and behavioral factors is the provision of dental care. Regular dental checkups have shown as important to maintain good oral health [ 69 ]. Thus, caries management at the individual level, should include dietary counseling with sugars intake restriction, biofilm control and periodic checkups according to risk to promote oral and systemic health.…”
Section: Comprehensive Management Of Dental Caries As a Ncd Beyond Th...mentioning
confidence: 99%